2014
DOI: 10.1002/2013jb010682
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional resistivity structure and magma plumbing system of the Kirishima Volcanoes as inferred from broadband magnetotelluric data

Abstract: Broadband magnetotelluric (MT) measurements were conducted in 2010 and 2011 in the vicinity of Shinmoe-dake Volcano in the Kirishima volcano group, Japan, where sub-Plinian eruptions took place 3 times during 26-27 January 2011. By combining the new observations with previous MT data, it is found that an anomalous phase in excess of 90°is commonly observed in the northern sector of the Kirishima volcano group. Because the anomalous phase is not explained by 1-D or 2-D structure with isotropic resistivity media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 63 publications
5
63
0
Order By: Relevance
“…As with Aizawa et al (2008), we interpret that the resistive body consists of old and solidified magma and it forces the ascending magma to move eastward to the present conduit. Such structural controls were also suggested for Iwate Volcano, Japan (Aizawa et al 2009b), Aso Volcano, Japan , Kirishima Volcanoes, Japan (Aizawa et al 2014) and El Hierro Island (Canary Islands), Spain (Garcia-Yeguas et al 2014). Because the resistive body is located beneath the centre of the old stratovolcano, repeated intrusions of magma under the old eruption centre might have reduced the connected porosity of the area, causing it to become highly resistive.…”
Section: N T E R P R E Tat I O N O F R E S I S T I V I T Y S T Ru Cmentioning
confidence: 91%
“…As with Aizawa et al (2008), we interpret that the resistive body consists of old and solidified magma and it forces the ascending magma to move eastward to the present conduit. Such structural controls were also suggested for Iwate Volcano, Japan (Aizawa et al 2009b), Aso Volcano, Japan , Kirishima Volcanoes, Japan (Aizawa et al 2014) and El Hierro Island (Canary Islands), Spain (Garcia-Yeguas et al 2014). Because the resistive body is located beneath the centre of the old stratovolcano, repeated intrusions of magma under the old eruption centre might have reduced the connected porosity of the area, causing it to become highly resistive.…”
Section: N T E R P R E Tat I O N O F R E S I S T I V I T Y S T Ru Cmentioning
confidence: 91%
“…Aizawa et al . [] also indicated that there was a minimal RMS misfit as a function of model covariance parameters in their data set.…”
Section: Inversionmentioning
confidence: 99%
“…1A; e.g., Curtis, 1968;Cartwright and Hansen, 2006;Gudmundsson, 2006;Aoki et al, 2013;Aizawa et al, 2014;Muirhead et al, 2014;Tibaldi, 2015) or giant radiating dike swarms, which can facilitate lateral magma flow over hundreds to thousands of kilometers (e.g., Ernst and Baragar, 1992;Ernst et al, 1995;Macdonald et al, 2010). Recent field-, seismic reflection-, and modeling-based research further indicate that plumbing systems at shallow levels (typically <3 km depth), particularly those hosted in sedimentary basins, may instead be characterized by extensive sill complexes (e.g., Chevallier and Woodford, 1999;Smallwood and Maresh, 2002;Thomson and Hutton, 2004;Planke et al, 2005;Cartwright and Hansen, 2006;Kavanagh et al, 2006Kavanagh et al, , 2015Lee et al, 2006;Leuthold et al, 2012;Leat, 2008;Menand, 2008;Polteau et al, 2008a;Cukur et al, 2010;Bunger and Cruden, 2011;Gudmundsson and Løtveit, 2012;Muirhead et al, 2012;Svensen et al, 2012Svensen et al, , 2015Jackson et al, 2013;Magee et al, 2014;Zhao et al, 2014;Button and Cawthorn, 2015;Schofield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%